ANALISIS KINERJA SIMPANG TIGA TAK BERSINYAL PADA SIMPANG SALAKASO BERDASARKAN STANDAR PKJI 2023 - Isam Saepuloh; Ardin Rozandi (STKIP Subang, 2026)
Unsignaled intersections are intersections that are widely encountered in urban areas, one of which is the intersection of three unsignaled intersections on Jl. Raya Sukaraja - Sukabumi and Jl. Pempembangunan . This area is a commercial area that is crowded with shops, often experiencing congestion due to vehicle interaction and passenger pick-up and drop-off activities. This research aims to analyze the performance of intersections based on the 2023 Indonesian Road Capacity Guidelines (PKJI), the research directly surveys the field for three days, namely art, Wednesday and Saturday to obtain vehicle volume. From the results of the research on the Salakaso intersection, it can be known that the peak hours at the intersection on Saturday are 6249 hours 17.00-18.00 WIB. The results of the research and analysis obtained the capacity at the intersection was 2956.87 smp/hour, the volume of traffic flow reached 3614.6 smp/hour and the performance at the intersection during peak hours reached the degree of saturation of DJ 1.22. Based on the value of the degree of traffic performance saturation at the intersection of Jl. Raya Sukaraja – Sukabumi and Jl. Pembangunan of 1.22, because the DJ value exceeds 0.85 is not in accordance with the provisions suggested in the 2023 Indonesian Road Capacity Guidelines (PKJI), so there needs to be a replanning or improvement in the performance of the intersection with other alternatives.